Maintenance management model based on Lean Manufacturing to increase the productivity of a company in the Plastic sector - Ames, Victor (2019)
The current demand of the plastic sector has been increasing, managing to exceed the productivity of SMEs in developing countries such as Peru. Within this framework, the demand is greater than the supply due to the low production of the companies, which present a high index of hours due to lack of maintenance of the machines. The purpose of solving the main problem is to reduce the hours of low productivity that represent a great monetary loss for the company. That is why, by implementing this maintenance management model that is based on Lean Manufacturing, it will allow for a broad competitive advantage in the sector. This model was validated by implementing the TPM and SMED tools of the Lean Manufacturing philosophy within the plastics plant, achieving results that determine the degree of improvement of productivity in the company. Finally, after having validated the model, it is concluded that it could increase the capacity used by the company by 20% with the reduction of the changes.